Rekonstruksi Pendidikan Islam di Sekolah Dasar dalam Membentuk Karakter Religius Anak di Era Digital - Sapiuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has brought significant changes to children’s learning patterns and social behavior, which have implications for the process of religious character formation in elementary schools. Islamic education at the elementary level plays a strategic role in instilling religious values; however, conventional approaches are increasingly considered less responsive to the challenges of the digital era. This study aims to (1) identify the challenges of religious character formation among children in the digital era, (2) analyze Islamic education concepts that are relevant to the internalization of religious values in elementary school students, and (3) formulate directions for reconstructing Islamic education that are adaptive and contextual. This research employs a qualitative approach using a Systematic Literature Review (SLR) method. Data were obtained from scholarly journal articles, and the analysis was conducted through content analysis and thematic synthesis. The findings indicate that the digital era influences children’s religious behavior, discipline, and moral sensitivity, while Islamic education in elementary schools remains largely dominated by cognitive and normative approaches. Therefore, a reconstruction of Islamic education is needed through the integration of religious values, digital literacy, and adaptive pedagogical strategies. This reconstruction emphasizes curriculum renewal, strengthening teachers’ competencies, and utilizing technology as a value-based learning medium to enhance the formation of children’s religious character in the digital era.